2016
DOI: 10.3892/etm.2016.4018
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cells and myeloid regulatory cells in cancer and autoimmune disorders

Abstract: Abstract. Myeloid-derived suppressor cells (MDSCs) were originally described as a heterogeneous population of immature cells derived from myeloid progenitors with immune-suppressive functions in tumor-bearing hosts. In recent years, increasing number of studies have described various populations of myeloid cells with MDSC-like properties in murine models of cancer and autoimmune diseases. These studies have observed that the populations of MDSCs are increased during inflammation and autoimmune conditions. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 128 publications
(106 reference statements)
0
14
0
1
Order By: Relevance
“…Many studies have demonstrated that MDSCs are significantly increased in malignancies, autoimmune disease and viral infectious disease . Khaled et al found that G‐MDSCs, but not M‐MDSCs, were significantly increased in circulation and showed increased tumour infiltration in pancreatic cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that MDSCs are significantly increased in malignancies, autoimmune disease and viral infectious disease . Khaled et al found that G‐MDSCs, but not M‐MDSCs, were significantly increased in circulation and showed increased tumour infiltration in pancreatic cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…MDSCs have been shown to expand systemically in various pathologies such as infection [89,90], sepsis [91], and autoimmune disorders [92]. All the major cytokines that are involved in the normal hematopoiesis and proliferation of MDSCs, such as macrophage colony stimulating factor and granulocyte macrophage colony stimulating factor (GM-CSF), are highly expressed in GBM [93].…”
Section: Mdscs In Glioma Progressionmentioning
confidence: 99%
“…Furthermore, L-arginine depletion by Arg1 triggers the production of ROS through iNOS. Several tumor-derived growth factors, such as TGF-β, IL-6, IL-10, and GM-CSF, can increase the production of ROS [92].…”
Section: Mdsc-mediated Immunosuppression and Therapy Resistance In Glmentioning
confidence: 99%
“…The studies in mice show that MDSCs can increase the generation of Treg through a TGF‐β1‐dependent mechanism, while M‐MDSCs induce antigen‐pulsed Treg by producing NO . Besides, it suggests that CD40/CD40L may have a critical role in inducing Treg, because M‐MDSCs from CD40‐deficient mice cannot promote the proliferation of Treg cells …”
Section: Main Functional Characteristics Of Mdscsmentioning
confidence: 99%